Calculation of the maximally regular net on the sphere - POHÁNKA, Vladimír (Contributions to Geophysics and Geodesy, 2021)
The method used for the numerical calculation of the maximally regular net on the sphere is described and the results of the calculation are presented. The calculation required to develop the fixed point representation of real numbers and procedures for manipulation with such data. The results include several empirical formulae for the number of occurences of values of coordinates of vertices of the net and of values of scalar product of radius-vectors of neighbouring vertices, whose theoretical derivation seems to be very difficult.